LOVINA: Location-aware Virtual Navigation system based on active RFID. (11th November 2011) - Wang, Ching-Sheng
This paper presents a novel application called LOVINA for RFID computing that integrates RFID positioning technology and virtual reality. Using a museum as an example, we develop a 3D virtual navigation system that supports indoor RFID localisation. If a user is carrying a notebook or mobile device while walking through an exhibition room, the system can update the user's position accurately. This information can be used to guide users as they near particular historical objects; for example, the system can trigger special information that alerts users and helps them experience real and virtual historical relics, buildings, and incidents more completely.